2023
DOI: 10.1101/2023.01.03.522509
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Liver Fibroblast Growth Factor 21 (FGF21) is Required for the Full Anorectic Effect of the Glucagon-Like Peptide-1 Receptor Agonist Liraglutide in Male Mice fed High Carbohydrate Diets

Abstract: Glucagon-like peptide-1 receptor (GLP-1R) agonists and fibroblast growth factor 21 (FGF21) confer similar metabolic benefits. Studies report that GLP-1RA induce FGF21. Here, we investigated the mechanisms engaged by the GLP-1R agonist liraglutide to increase FGF21 levels and the metabolic relevance of liraglutide-induced FGF21. We show that liraglutide increases FGF21 levels via neuronal GLP-1R activation. We also demonstrate that lack of liver Fgf21 expression confers partial resistance to liraglutide-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Protein ingestion preferentially favours gastrin and cholecystokinin, whereas carbohydrate ingestion preferentially favours gastric inhibitory polypeptide and glucagon-like peptide 1 (GLP-1). Interestingly, GLP-1 (and GLP-1 agonists) in turn act on feeding centres in the brain, promoting hepatic FGF21 production via mechanisms including adrenal cortex production of glucocorticoids [70]. One potential candidate as a systemic protein satiety hormone is glucagon, which has been implicated in the control of macronutrient selection [71] and contributes to a liver-islet alpha cell axis for the control of plasma amino acid levels, in which a high plasma amino acid level induces alpha cell hyperplasia and, in turn, increased glucagon production to stimulate amino acid breakdown [72].…”
Section: The Power Of Proteinmentioning
confidence: 99%
“…Protein ingestion preferentially favours gastrin and cholecystokinin, whereas carbohydrate ingestion preferentially favours gastric inhibitory polypeptide and glucagon-like peptide 1 (GLP-1). Interestingly, GLP-1 (and GLP-1 agonists) in turn act on feeding centres in the brain, promoting hepatic FGF21 production via mechanisms including adrenal cortex production of glucocorticoids [70]. One potential candidate as a systemic protein satiety hormone is glucagon, which has been implicated in the control of macronutrient selection [71] and contributes to a liver-islet alpha cell axis for the control of plasma amino acid levels, in which a high plasma amino acid level induces alpha cell hyperplasia and, in turn, increased glucagon production to stimulate amino acid breakdown [72].…”
Section: The Power Of Proteinmentioning
confidence: 99%
“…A 1.5 mg/kg dose of FGF21 provides maximal neuroprotection and cognitive improvements in normothermic neonatal and adult rodent brain injury models, and this dose is estimated to yield peak serum levels of greater than 200,000 pg/mL (46). This observation suggests that alternative strategies to raise FGF21 levels (e.g., cooling or glucagon-like peptide-1) agonists may be inferior because they yield levels 40–200X below the threshold needed to engage all of FGF21’s protective effects (47). Furthermore, rapidly achieving an optimal therapeutic FGF21 concentration at normothermia or before the initiation of cooling may be essential.…”
Section: Fgf21—preclinical Findingsmentioning
confidence: 99%
“…The most promising effects of those "pre-drugs" are the attenuation of hyperlipidemia and the improvement of insulin sensitivity. We and others have also reported that hepatic FGF21 expression can be regulated by glucagon-like peptide-1 (GLP-1) receptor agonists (GLP-1RAs), including both exenatide and liraglutide (12)(13)(14)(15). Utilizing the liver speci c Fgf21 knockout mouse model, we have demonstrated recently that hepatic FGF21 is required for liraglutide in improving energy homeostasis in male mice with obesogenic diet challenge, making hepatic FGF21 as a "central molecule" for both GLP-1R-based drugs and diet interventions (12).…”
Section: Introductionmentioning
confidence: 99%